THE COMPLETE STORY: A POPULATION‐ BASED PERSPECTIVE ON SCHOOL PERFORMANCE AND EDUCATIONAL TESTING - Roos, Noralou; Brownell, Marni; Guevremont, Anne; Fransoo, Randy; Levin, Ben; MacWilliam, Leonard; Roos, Leslie (Canadian Journal of Education/Revue canadienne de l’éducation, 2006)
All children born in Manitoba in 1984 were tracked for 18 years to assess their grade‐ 12 performance on a provincial examination according to a student’s socio‐economic status. The proportion of youths in families receiving social assistance judged to have passed their language arts exam dropped from 80 per cent to 12 per cent, depending on whether one counts only those in the cohort who took the test on time in 2002 or all youths born in 1984 who should have taken the test in 2002. Getting better data on performance and doing something about the discrepancies should become a Canadian priority. Key words: educational opportunity, exam performance, socio‐economic status, testing, longitudinal studies Tous les enfants nés au Manitoba en 1984 ont été suivis sur une période de 18 ans en vue d’évaluer leur rendement en 12e année lors d’un examen provincial, tenant compte de leur statut socioéconomique. La proportion de jeunes issus des familles recevant de l’aide sociale et considérés comme ayant réussi leur examen au plan des compétences linguistiques passe de 80 % à 12 %, selon que l’on compte seulement ceux qui, dans la cohorte, ont subi l’examen à temps en 2002 ou tous les jeunes nés en 1984 qui auraient dû subir l’examen. En matière d’égalité des chances, la performance du système scolaire actuel au Canada laisse à désirer. Mots clés: possibilités éducatives, résultats d’examen, statut socioéconomique, analyse longitudinale.